Roles and mechanisms of dopamine receptor signaling in catecholamine excess induced endothelial dysfunctions: research paper - Yang, Zhen; Li, Yingrui; Huang, Mengying; Li, Xin; Fan, Xuehui; Yan, Chen; Meng, Zenghui; Liao, Bin; Hamdani, Nazha; Yang, Xiaoli; Zhou, Xiao-Bo; El-Battrawy, Ibrahim; et al. (International journal of medical sciences, 2024)
Endothelial dysfunction may contribute to pathogenesis of Takotsubo cardiomyopathy, but mechanism underlying endothelial dysfunction in the setting of catecholamine excess has not been clarified. The study reports that D1/D5 dopamine receptor signaling and small conductance calcium-activated potassium channels contribute to high concentration catecholamine induced endothelial cell dysfunction. For mimicking catecholamine excess, 100 μM epinephrine (Epi) was used to treat human cardiac microvascular endothelial cells. Patch clamp, FACS, ELISA, PCR, western blot and immunostaining analyses were performed in the study. Epi enhanced small conductance calcium-activated potassium channel current (ISK1-3) without influencing the channel expression and the effect was attenuated by D1/D5 receptor blocker. D1/D5 agonists mimicked the Epi effect, suggesting involvement of D1/D5 receptors in Epi effects. The enhancement of ISK1-3 caused by D1/D5 activation involved roles of PKA, ROS and NADPH oxidases. Activation of D1/D5 and SK1-3 channels caused a hyperpolarization, reduced NO production and increased ROS production. The NO reduction was membrane potential independent, while ROS production was increased by the hyperpolarization. ROS (H2O2) suppressed NO production. The study demonstrates that high concentration catecholamine can activate D1/D5 and SK1-3 channels through NADPH-ROS and PKA signaling and reduce NO production, which may facilitate vasoconstriction in the setting of catecholamine excess.